Implementation fidelity of nutritional counselling, iron and folic acid supplementation guidelines and associated challenges in rural Uasin Gishu County Kenya - Roselyter Monchari Riang’a; Anne Kisaka Nangulu; Jacqueline E. W. Broerse (BMC Nutrition, 2020)
Abstract Background Implementation fidelity which is defined as the degree to which programmes are implemented as intended is one of the factors that affect programme outcome, thus requiring careful examination. This study aims to acquire insight into the degree to which nutritional counselling and Iron and Folic Acid supplementation (IFAs) policy guidelines during pregnancy have been implemented as intended and the challenges to implementation fidelity. Methods Data were collected in rural Uasin Gishu County in the western part of Kenya through document analysis, questionnaires among intervention recipients (n = 188) and semi-structured interviews with programme implementers (n = 6). Data collection and analysis were guided by an implementation fidelity framework. We specifically evaluated adherence to intervention design (content, frequency, duration and coverage), exposure or dosage, quality of delivery and participant responsiveness. Results Coverage of nutritional counselling and IFAs policy is widespread. However, partial provision was reported in all the intervention components. Only 10% accessed intervention within the first trimester as recommended by policy guidelines, only 28% reported receiving nutritional counselling, only 18 and 15% of the respondents received 90 or more iron and folic acid pills respectively during their entire pregnancy period, and 66% completed taking the IFAs pills that were issued to them. Late initial bookings to antenatal care, drug stock shortage, staff shortage and long queues, confusing dosage instructions, side effects of the pills and issuing of many pills at one go, were established to be the main challenges to effective implementation fidelity. Anticipated health consequences and emphasis by the health officer to comply with instructions were established to be motivations for adherence to nutritional counselling and IFAs guidelines. Conclusions Implementation fidelity of nutritional counselling and IFAs policy in Kenya is generally weak. There is need for approaches to enhance early access to interventions, enhance stock availability, provide mitigation measures for the side effects, as well as intensify nutritional counselling to promote the consumption of micronutrient-rich food sources available in the local environment to substitute for the shortage of nutritional supplements and low compliance to IFAs.